Dinamika Sosial Budaya Tukang Cukur Madura di Ternate - Suharlin Ode Bau; Jamain Warwefubun (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
The social approach of Madura barbers in Ternate in carrying out their work colors the social dynamics of the community. This research aims to examine the socio-cultural dynamics of the Madura barber community in Ternate by using historical research methods consisting of heuristics, criticism, interpretation, and historiography. The social history approach is used to extract information from informants.  The results showed that the Madura barbers brought not only their technical skills, but also cultural values such as peer-to-peer solidarity and a close social relationship system. This dynamic also involves an acculturation process with Ternate's local culture, although it still maintains Madura identity and traditions. The social transformation that occurs among Madura barbers reflects that migrant groups can maintain their culture while interacting with the dominant culture in their new environment. In addition, it provides insight into socio-cultural diversity and the role of migrant communities in shaping cultural identity in overseas areas.